P363 The minimal invasive surgery in combination with negative pressure wound therapy for perianal fistulas in Crohn's colitis lead to the fast introduction of the biological treatment and improve the results. (25th January 2019) - Banasiewicz, T; Paszkowski, J; Hermann, J; Cwalinski, J; Eder, P; Stawczyk-Eder, K; Waszak, K; Dobrowolska, A
Abstract: Background: Perianal fistula in Crohn's colitis (CC) seems be common complication. The aim of the study was determine the effectiveness of the minimal invasive surgical treatment with vacuum technique and subsequent biological therapy in CC patients with perianal fistulas. Methods: In total, 59 CC patients were admitted due to perianal fistula (symptomatic or asymptomatic with abscess) to surgical Department. In 24 patients (Group I), minimal invasive surgical treatment was performed (excision of external opening and fistula tract, application of vacuum therapy), than after 2–4 weeks biological therapy was introduced. In 14 patients (Group II), standard surgical procedures were performed (excision with flap, seton drainage). The biological therapy was introduced depend on the wound healing after 6–16 weeks; in 21 patients only surgical procedure (excision with flap, seton drainage) was performed. Follow-up for every patient was minimum 12 months. Results: Fistula recurrences were observed in 12% in Group I; in 35% in Group II and in 45% in Group III. Faecal incontinence was reported in 0% (Group I), 21% (Group II) and 20% (Group III) . Conclusions: Use of the vacuum technique ('superficial' or 'endosponge') in the surgical treatment in CC patients with perianal fistulas is effective, safe, and well accepted.